Application of ultrasound measurement of optic nerve sheath diameter to guide hyperosmolar therapy in children with intracranial hypertension - Hua, Yanping; Wang, Jiawei; Li, Yong; Shen, Yuhao; Jiang, Leihua; Wu, Jiaowei (Frontiers in Pediatrics, 2025)
PurposeAssessing the Clinical Value of Optic Nerve Sheath Diameter (ONSD) Ultrasonography in Pediatric Severe Intracranial Hypertension Monitoring and Treatment Efficacy Evaluation.MethodsThis study included 86 critically ill children with intracranial hypertension, and used bedside ultrasound to dynamically monitor the diameter of the optic ONSD to evaluate the status of intracranial hypertension. The experimental group (n = 33) underwent three daily ONSD ultrasound monitoring throughout the treatment process, with a baseline value of >5.2 mm set as the intervention threshold based on the guidelines of the American Society for Neurocritical Care; The control group (n = 53) was monitored using traditional clinical signs. The efficacy evaluation was conducted using the National Institute of Health Stroke Scale (NIHSS), and core indicators such as the duration of neurological function recovery, Intensive Care Unit (ICU) hospitalization period, and incidence of complications were comprehensively compared between the two groups of children.ResultONSD measurements, hyperosmolar agent [mannitol, hypertonic saline(HTS)] were adjusted accordingly. The treatment group demonstrated significantly shorter duration of hyperosmolar agents compared to controls. Although the ultrasound-guided group showed reduced hospitalization duration relative to the control group, this difference did not reach statistical significance. Neurological outcomes evaluated by discharge Glasgow Coma Scale (GCS) scores revealed clinically meaningful differences: the treatment group exhibited higher proportion of fully conscious patients and lower incidence of consciousness with both parameters showing statistical significance.ConclusionThe implementation of optimized neurological intensive care protocols incorporating multimodal monitoring demonstrates significant prognostic benefits. ONSD measurement offers clinical advantages as a rapid, non-invasive modality for detecting intracranial pressure fluctuations, establishing its utility in therapeutic monitoring for pediatric patients with severe intracranial hypertension.